1979
DOI: 10.1159/000241221
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Rat Adrenal Growth and Steroidogenesis <i>in vitro </i>after Maternal Dexamethasone Treatment

Abstract: Two groups of female rats were treated with dexamethasone phosphate (DEX) for 24 h. One group received DEX in drinking water (10 μg/ml) on the 15th day of pregnancy (DEX15–16), and the second group on the 17th day of pregnancy (DEX17–18). The mothers and fetuses were sacrificed on the 20th and 22nd days of pregnancy. DEX reduced adrenal weights and concentration of corticosterone in plasma of the treated females and their fetuses. Fetal body weight was also reduced. However, the lightest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other studies with dexamethasone treatment in fetal rats and guinea pigs have shown that fetal adrenal suppression is related to the dose, stage of gestation and duration of recovery period [34,36,48]. Fetal rhesus mon keys exposed to maternal betamethasone doses comparable to those used in human pregnancy have variously shown either lack of suppression [39] or suppression [29,30] of adrenal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with dexamethasone treatment in fetal rats and guinea pigs have shown that fetal adrenal suppression is related to the dose, stage of gestation and duration of recovery period [34,36,48]. Fetal rhesus mon keys exposed to maternal betamethasone doses comparable to those used in human pregnancy have variously shown either lack of suppression [39] or suppression [29,30] of adrenal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal adrenal growth is also inhibited by high levels of circulating maternal corticosteroids which can cross the placenta and block fetal pituitary stimulation of the adrenals (Zarrow et al, 1970;D'Angelo et al, 1973;Milkovic and Domac, 1973;Klepac and Milkovic, 1979).…”
mentioning
confidence: 99%